Rational Design of a Flexible CNTs@PDMS Film Patterned by Bio‐Inspired Templates as a Strain Sensor and Supercapacitor. Issue 18 (4th April 2019) - Zhang, Chenjun; Li, Hui; Huang, Aoming; Zhang, Qiao; Rui, Kun; Lin, Huijuan; Sun, Gengzhi; Zhu, Jixin; Peng, Huisheng; Huang, Wei
Abstract: Flexible devices integrated with sensing and energy storage functions are highly desirable due to their potential application in wearable electronics and human motion detection. Here, a flexible film is designed in a facile and low‐cost leaf templating process, comprising wrinkled carbon nanotubes (CNTs) as the conductive layer and patterned polydimethylsiloxane (PDMS) with bio‐inspired microstructure as a soft substrate. Assembled from wrinkled CNTs on patterned PDMS film, a strain sensor is realized to possess sensitive resistance response against various deformations, producing a resistance response of 0.34%, 0.14%, and 9.1% under bending, pressing, and 20% strain, respectively. Besides, the strain sensor can reach a resistance response of 3.01 when stretched to 44%. Furthermore, through the electro‐deposition of polyaniline, the CNTs film is developed into a supercapacitor, which exhibits a specific capacitance of 176 F g −1 at 1 A g −1 and a capacitance retention of 88% after 10 000 cycles. In addition, the fabricated supercapacitor shows super flexibility, delivering a capacitance retention of 98% after 180° bending for 100 cycles, 95% after 45° twisting for 100 cycles, and 98% after 100% stretching for 400 cycles. The superior capacitance stability demonstrates that the design of wrinkled CNTs‐based electrodes fixed by microstructures is beneficial to the excellent electrochemical performance. Abstract : A cost‐efficient bio‐inspired templating strategy is employed to fabricate microstructures onto flexible polydimethylsiloxane films using leaves as templates. The film is developed into a strain sensor when paved with wrinkled carbon nanotubes. After electrodepositon of electroactive polyaniline, it can be further assembled into a supercapacitor, indicating a potential application for bifunctional devices with sensing and energy storage functions.